Competition time of weeds with upland rice - Alcântara, Elifas Nunes de; Carvalho, Douglas Antônio de (Pesquisa Agropecuaria Brasileira, 2014)
One experiment was carried out at Lavras, MG, in order to determine the critical competition time of local weeds with upland rice (Oryza sativa L.), grown on Dark Red Latosol with 3,2% of organic matter. The experiment design was in randomized blocks with 14 treatments replicated four times. The treatments were growing rice with and without weeds for different periods. Plant density was 50 kg of rice seeds/ha with 0.5 m between lines. Ninety percent of the weeds was large crabgrass (Digitaria  sanguinalis (L.) Scop.) being only 10% composed of alexandergrass (Brachiaria plantaginea (Link) Hitch), beggarticks (Bidens pilosa L.), red tasselflower (Emilia sonchifolia DC.). Mexican clover (Richardia brasiliensis Gomez) and Borreria alata (Aubl.) DC. The results showed that the height of rice plants was not affected by the presence of weeds but the number of panicles per m2 and grain yield were reduced. The competition period was from 40 days after seedling emergency.
Keywords: oryza sativa; dark red latosol soil; competition